APPLICATION OF STRATEGIC COSTS OF GLOBAL MARKET TO PERUVIAN INDUSTRY - Arrarte Mera, Raúl Alberto (2012)
This applied research with qualitative approach was funded in 2011 by the Research Vice Chancellor of the Major National University of Saint Marc (Universidad Nacional Mayor de San Marcos) and selected by an international jury for the XIII ALAFEC General Assembly, held in Buenos Aires, Argentina, from 9 to 12 October 2012. The research used was descriptive-explanatorydocumentary. The methods used were the inductive and deductive. The evaluated population reached 59 companies in the chemical, textile, dairy, cement, fishing, beer, oil and steel sectors, which listed on the Lima Stock Exchange, Peru. Our specific objectives are: a) Identify the set of activities that creates the value chain. b) Examine the causes of costs that cause its incurrence and that do not add value to the company. c) Analyze the strategic positioning that the company in its industry. We conclude that only 53% of these industries have positive economic value added to a TEA ( ) of 10%. And this drops to 44%, when the TEA rises to 12%.